MENGUKUR TINGKAT SOCIAL VALUE CHAIN MELALUI OPTIMALISASI PENGELOLAAN ZISWAF DI INDONESIA - Syamsuri; Husnul Khotimah; Dwi Noviatul Zahra; Lamya Nurul Fadhilah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
In the Indonesian context, Islamic social finance sector is synonymous with zakat and waqf institutions. This is influenced by explanation of two regulations in Indonesia related to Islamic social finance, namely Law no. 23 of 2011 concerning Zakat Management and Law no. 41 of 2004 concerning waqf. In addition to zakat, waqf also has no less great potential to support the development of halal industry in Indonesia. With characteristics of being relatively flexible in use, the potential for waqf is much greater even though collection is still relatively low compared to its potential. Several important issues that arise in halal industry in Indonesia are lack of competitiveness of halal products in Indonesia in global market, one of which can be caused by high production costs. The research method used is descriptive qualitative by using primary reference sources, namely reading and taking notes and processing research materials in library such as books, news, and others. The analytical technique used is content analysis of the literature related to zakat and taxes in Islam. Thus, it can be concluded that the ZISWAF sector has great potential to encourage the development of the halal industry in Indonesia. However, this potential will only be realized if there is an ecosystem and policies that support this. For this reason, before formulating strategic policies and encouraging the creation of the required ecosystem, the existing strengths and challenges need to be identified properly. This will be further discussed in the section on zakat and waqf development strategies